Three dimensional evaluation of accuracy of bracket positioning - Kapil Kamal Kishor Fafat; Deepali Jain; Susmita Kumari Pandit; Rythm Kharbanda; Pragya Trivedy; Ekta Gupta (Journal of Pharmacy and Bioallied Sciences, 2023)
Introduction: The success of orthodontic treatment depends on accurate bracket placement, so researchers are constantly exploring new direct and indirect bonding methods with the help of cutting-edge imaging technologies like cone beam computed tomography (CBCT), which provides full three-dimensional visualization of tissues down to the root of the tooth. Aim: The primary goals of this analysis are to determine the degree of section angulation and adhesive thickness, as well as the accuracy of the vertical and flat section positions. The correlation between total clinical crown height, minor edge to focus of section, and minimum edge to complete curve crown length is one of several possible goals of this investigation (FACC). Materials and Methods: Currently, 10 patients aged 15-30 who needed fixed appliance treatment were enrolled in an in vivo research conducted by the orthodontics department. Cases with and without extractions of the crooked teeth were counted. Full mouth analysis is being used in this investigation. Ten patients were selected at random and placed in either Group A (the study group) or Group B (the control group) (control group). Group A bonds are more indirect, whereas group B bonds are more like “normal” direct bonds. We used a Canon 700D camera, a biocompatible transparent 3D printing resin, and a 3M Gemini MBT.022 in bracket kit for CT scanning and imaging. Brackets are placed by experienced orthodontists in both treatment groups. Result: There is a statistically significant (P 0.05) difference between the indirect and direct bonding group when all five factors are taken into account, with the indirect bonding group demonstrating superiority in terms of accuracy. Conclusion: The results of the current investigation support the premise that there is a clinically significant difference between direct bonding and 3D indirect bonding in terms of bracket placement accuracy.